The concepts of poverty used by the ANC government between 1994 and 2004 - Kenyon, Steven (Department of Political Studies, 2014)
The choice of how poverty is conceptualised can have a significant effect on who is defined as poor and consequently who is targeted by government policies aimed at poverty eradication. This thesis examines the discourses of poverty used by the ANC government in its first decade in power and analyses what concepts of poverty underpin those discourses. By examining what concepts are used, this thesis lays a foundation for understanding what effect (if any) the concepts of poverty used by the ANC government might have on its efforts to combat poverty.